Analisis Teks Berita Pada Media Massa Koran Solopos Berdasarkan Register Dan Fungsi Bahasa Serta Implementasinya Sebagai Bahan Ajar Di Sma - ASVIVIANA, VIONA RIKA; , Prof. Dr. H. Abdul Ngalim, MM.,M.Hum (2016)
There are three objectives in this study. (1) Describe the type of analysis registers and function of language in the mass media Solopos newspaper.(2) Describe the appropriate usage register and function of language in the mass media Solopos newspaper. (3) Describe the types of registers and analyzes the implementation og language function in the mass media Solopos newspaper as teaching material in high school. The data in this study is data software (soft data) in the form of words or phrases on the news content Solopos news paper, while the source of the data in this study report text on the mass media Solopos newspaper. Data collection techniques used in this study are engineering and technical literature refer to note. Data analysis techniques with methods agih be read many. Data were analyzed using methods shared with expanding techniques. It can be concluded. (1) Research based on paper hearts listing Solopos there are several types register, ie legal, sports, medicine, education, politics, artists, religious, journalists, and economics. From the findings of the analysis, can be known that compared with registering lie, listing the many found is the law and sport. There are six function of language that functions as a delivery mean, sincerely, introduction, solidarity, uneg-uneg, mirror civilization was. (2) The accuracy of the register usage dominant, but there are three incorrect data include malpractice, journalist, and poured. (3) Implementation of RPP manufacture according KI 3 and KD 3.3 class XII. Keywords: register, language function, implementation.